Optimising Bcrypt Parameters: Finding the Optimal Number of Rounds for Enhanced Security and Performance - Listiawan, Indra; Zaidir, Zaidir; Winardi, Sugeng; Diqi, Mohammad (Compiler, 2024)
Recent advancements in the field of information security have underscored the imperative to fine-tune Bcrypt parameters, particularly focusing on the optimal number of rounds as the objective of research. The method of research is a Brute Force Search method to find the optimal value of bcrypt rounds. The primary focal point of optimization lies in the number of Bcrypt rounds due to its direct impact on security levels. Elevating the number of rounds serves to fortify the security of the Bcrypt algorithm, rendering it more resilient against brute-force attacks. The execution of the Bcrypt rounds in the experimental method mirrors real-world scenarios, specifically in the evaluation of Bcrypt parameters with a focus on entropy assessment of the hash. The selection of the number of rounds should consider the specific needs of the system, where security takes precedence or faster performance is a crucial factor.